(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2018)
The civil engineer has many diverse and important encounters with soil. Every building structure has to be constructed on soil foundation soil depending upon site conditions. Soil is therefore, ultimate foundation material which supports the structure. The proper functioning of the structure will therefore depend critically on the success of the foundation element resting on the sub soil. It is therefore, necessary to know the bearing capacity of the soil, the pattern of stress distribution in the soil beneath the loaded area, the probable settlement of the foundation, effect of vibration and water level. The present project work is aimed towards study of selection criteria of foundation types based on soil conditions, acceptance criteria of different parameters of soils. The method used to determine bearing capacity is IS Code Method which is described in detail, while other methods like Terzaghi, Mayeroff and Vesics methods are briefly described. Load calculations are carried out for a G+2 residential building and G+3 commercial building. The results are obtained for various values of specific weight, cohesion and angle of internal friction. The type of foundation like shallow strip footing resting on different soil like cohesion-less soil can be suggest by using the software. The parameter of different types of soil can be input for this and can obtained from the analysis of soil. In conclusion, the need for a proper evaluation methodology for calculation of correlation lengths of soil properties and their influence in foundation design is highlighted. The calculation for foundation on different soil by using this software and without software can be compare and time require for this calculation can also be compare.